2019
DOI: 10.32598/hdq.4.3.119
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity to Establish Health, Safety and Environment Management Major at the University of Social Welfare and Rehabilitation Sciences

Abstract: Researchers have already highlighted the safety and health issues in workplaces. The necessity of these issues and their close relations to the environment have more transparently called for the management control of three critical dimensions of Health, Safety, and the Environment (HSE). Furthermore, following the rapid development of technology and the complexity of the activities tailored to the needs of companies and industries, a set of guidelines called HSE was developed to minimize the damages to human, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This data note aims to provide comprehensive information about the Health, Safety and Environment (HSE) risk assessment. Such these data sets are necessary for accident prevention and decrease the harmful impacts such as death, injuries and damages to structures and equipment at academic settings [2,3]. Also, such these risk assessment results promote information sharing across the university systems about best practices to mitigate the vulnerability of hazards [4].…”
Section: Objectivementioning
confidence: 99%
“…This data note aims to provide comprehensive information about the Health, Safety and Environment (HSE) risk assessment. Such these data sets are necessary for accident prevention and decrease the harmful impacts such as death, injuries and damages to structures and equipment at academic settings [2,3]. Also, such these risk assessment results promote information sharing across the university systems about best practices to mitigate the vulnerability of hazards [4].…”
Section: Objectivementioning
confidence: 99%
“…The notion of employee well-being at work promotes the benefits of having a healthy workforce to enterprises. [ 23 , 24 ] Employee well-being at work, according to Athota et al, [ 25 ] is the physical and mental health of the work force; consequently, employees should work in a stress-free and physically safe setting. So that, the aim of this study is to determine the extent to which nurses are aware of their comfort, HSB, and their psychological well-being in order to assist staff in avoiding career burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous research suggested conducting regular exercises according to defined accident scenarios might be useful in providing preparedness among people at the time of incidents [10,11]. The occurrence of tragic accidents in Iranian universities revealed that they have been slow to apply safety and health principles to the management of risks within processes [3,4,12,13].…”
Section: Introductionmentioning
confidence: 99%